Applications of the Jupiter Global Ionosphere‐Thermosphere Model: A case study of auroral electron energy deposition. Issue 2 (7th February 2017) - Egert, Austin; Waite, J. Hunter; Bell, Jared
Abstract: We investigate auroral energy deposition by using a nonhydrostatic global atmospheric model coupled to a two‐stream electron transport model. We present several electron beam study cases, discussing energy flux and electron energy effects on the ion and neutral densities, the atmospheric thermal profile, H3 + and hydrocarbon infrared (IR) emissions, H2 far ultraviolet (FUV) emissions and color ratios, and vibrationally excited molecular hydrogen. Using the nonhydrostatic Jupiter Global Ionosphere‐Thermosphere Model, we find that FUV spectral characteristics consistent with previous Hubble Space Telescope results derive primarily from electrons with energies above 10 keV, over energy fluxes of 10–100 erg/cm 2  s, while IR emissions are predominantly due to electrons with energies below 10 keV, over energy fluxes of 10–100 erg/cm 2  s. Electrons with energies below about 10 keV produce enough H2 ( ν ) to deplete the H + population, modifying the ionospheric composition, and consequently the H3 + emissions, which can be used to directly relate H2 vibrational excitation to auroral observations. New observations by Juno will provide better electron energy distributions to constrain the electron energy spectrum and magnitude at the upper boundary of the model and simultaneously provide a determination of the FUV and IR spectra that can be cross‐correlated with the observations. Plain Language Summary: Jupiter's aurora is a result of a whole lot of energy entering the atmosphere. The aurora is observed in infrared, visible light, ultraviolet, and even X‐rays. Each of these types of aurora may be tied to a different source, and in this paper, we investigate the infrared and ultraviolet sources. In order to connect the sources to data gathered by satellites, we simulate a number of physical processes, produce an artificial aurora, and then compare it to the actual auroral observations collected from the satellites. Important processes in this simulation include atmospheric chemistry, electrons that bring the energy into the atmosphere, and physical dynamics that distribute the energy. We found that we can produce infrared and ultraviolet aurora similar to satellite observations if we choose an appropriate range of electron energies. Key Points: We investigated auroral energy deposition effects using a nonhydrostatic atmospheric model H2 ( ν ) modifies the atmospheric densities, particularly the H + and H3 + densities, which subsequently modify infrared emissions H3 + column emissions and H2 spectrum color ratios and intensities are consistent with Earth‐based observations